Social influences on changes in youth athletes` motivation and well being - Amorose, A. J.; McDavid, M. l. (Research Quarterly for Exercise and Sport, 2011)
Despite a commonly held belief that sport participation leads to positive experiences and developmental outcomes, little is known about: (a) how and why sport participation leads to more or less positive outcomes, and (b) how adults in sport— namely parents and coaches—influence these outcomes in youth. Grounded in self-determination theory, the purpose of this study was to examine whether changes in motivation and well being (i.e., burnout and self-esteem) of adolescent sport participants across a season are predicted by perceived autonomy support from parents and coaches and the satisfaction of youth`s psychological needs for competence, autonomy, and relatedness. Athletes (N = 391; M age = 15.43 years; 60.9% female; 85.9% Caucasian) from a variety of school-sponsored sport teams completed valid and reliable questionnaires at the beginning and end of their competitive season. Path analysis results showed that perceived autonomy support from coaches positively predicted changes in athletes` psychological need satisfaction, which in turn positively predicted changes in their self-determined motivational orientation and self-esteem and negatively predicted changes in burnout. Autonomy support from mothers and fathers were nonsignificant predictors. The model, which fit the data well (SB ÷2 = 10.81, df = 9, p = .29, root mean square error of approximation = .02), accounted for 19-24% of the variation in need satisfaction changes and 8%, 6%, and 12% of the variation in changes in motivational orientation, self-esteem, and burnout, respectively. The results support the basic tenants of self-determination theory and highlight the important role played by coaches in determining whether sport participation results in positive or negative outcomes.